2023
DOI: 10.1002/ctm2.1233
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐β7 integrin treatment impedes the recruitment on non‐classical monocytes to the gut and delays macrophage‐mediated intestinal wound healing

Abstract: Background Closing mucosal defects to reach mucosal healing is an important goal of therapy in inflammatory bowel disease (IBD). Among other cells, monocyte‐derived macrophages are centrally involved in such intestinal wound healing. We had previously demonstrated that the anti‐α4β7 integrin antibody vedolizumab blocks the recruitment of non‐classical monocytes as biased progenitors of wound healing macrophages to the gut and delays wound healing. However, although important for the interpretation of disappoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The possible mechanism of action for nonclassical monocytes is associated with adhesion, production of complement components, and Fcγ-mediated phagocytosis. During the development of IBD, the intestinal epithelial barrier is compromised, allowing microbes to enter the tissue ( 33 ). Non-classical monocytes are recruited to the gut via α4β7 integrin, which transforms into macrophages and promotes wound healing ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism of action for nonclassical monocytes is associated with adhesion, production of complement components, and Fcγ-mediated phagocytosis. During the development of IBD, the intestinal epithelial barrier is compromised, allowing microbes to enter the tissue ( 33 ). Non-classical monocytes are recruited to the gut via α4β7 integrin, which transforms into macrophages and promotes wound healing ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…89 Moreover, it has been observed that non-classical monocytes tend to differentiate into macrophages that play a pivotal role in promoting wound healing. 90,91 Over time, monocytes also possess the capacity to differentiate into migratory antigen-presenting cells with dendritic cell characteristics, referred to as moDCs. 47 Consequently, within the inflammatory milieu of IBD, monocytes differentiation emerges as a complex and multifaceted process.…”
Section: Effect Of Inflammatory Microenvironment On Monocytes Differe...mentioning
confidence: 99%